Field water management and irrigation for improved rice systems: a training guide - Oke, Adebayo; Zemadim, Birhanu; Atengdem, P. B.; Amankwaa-Yeboah, P.; Cofie, Olufunke O. (International Water Management Institute, 2025)
This publication is designed to facilitate training in irrigation and water management of an irrigated rice field. It is to be used for the Training of Trainers (ToT). The information contained in the publication requires foundational knowledge of rice production, agricultural management, and irrigation practices. This training guide has five sections of relevant information to help you understand optimum water management to achieve higher rice productivity.